2014
DOI: 10.4049/jimmunol.1302253
|View full text |Cite
|
Sign up to set email alerts
|

Functional Avidity and IL-2/Perforin Production Is Linked to the Emergence of Mutations within HLA-B*5701–Restricted Epitopes and HIV-1 Disease Progression

Abstract: Viral escape from HIV-1-specific CD8+ T cells has been demonstrated in numerous studies previously. However, the qualitative features driving the emergence of mutations within epitopes are still unclear. In this study, we aimed to distinguish whether specific functional characteristics of HLA-B*5701-restricted CD8+ T cells influence the emergence of mutations in high-risk progressors (HRPs) versus low-risk progressors (LRPs). Single genome sequencing was performed to detect viral mutations (variants) within se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Interestingly, strong links between elevated frequency of cells expressing PD-1, in combination with CD38 and HLA-DR, was noted with reduced levels of both %CD4 and CD4 count. However, when analyzing %PD-1 + cells separately, there was only an association with %CD4, in line with our earlier observations that CD4/CD8 ratio and %CD4 correlate better with pathological T-cell phenotypes than CD4 count [ 33 ]. The simultaneous assessment of all markers and specific CD4 + T-cell populations using FLOCK analysis also revealed that PD-1-expressing populations, primarily the activated late-differentiated, were associated with low CD4 + T-cell levels in aviremic HIV-2 infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, strong links between elevated frequency of cells expressing PD-1, in combination with CD38 and HLA-DR, was noted with reduced levels of both %CD4 and CD4 count. However, when analyzing %PD-1 + cells separately, there was only an association with %CD4, in line with our earlier observations that CD4/CD8 ratio and %CD4 correlate better with pathological T-cell phenotypes than CD4 count [ 33 ]. The simultaneous assessment of all markers and specific CD4 + T-cell populations using FLOCK analysis also revealed that PD-1-expressing populations, primarily the activated late-differentiated, were associated with low CD4 + T-cell levels in aviremic HIV-2 infection.…”
Section: Discussionsupporting
confidence: 89%
“…Antibody capture beads (BD Biosciences) were used for compensation and FlowJo 8.8.7 (Tree Star, Ashland, Oregon, USA) for analyses. All manual gatings were based on fluorescence-minus-one gating strategies as described [ 33 , 34 ]. A typical gating strategy to distinguish CD4 + T cells is visualized in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Indisputably, T-cells exert strong selection pressure on HIV-1, generating HLA allele-restricted mutants that evade subsequent T-cell responses [48,49] . Emergence of HLA-B*5701-restricted variants has been linked to superior maintenance of IL-2 and Perforin, and persistence of polyfunctional CD8+ T-cell responses [50] . Superior virological control has been linked to greater functional avidity of the T-cell responses [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Antibody capture beads (BD Bioscience) were used for single-stain compensation controls. Flow cytometry data were analyzed with FlowJo 8.8.7 (Treestar) and when applicable, fluorescence minus one (FMO) gating strategies were used to set the manual gates93738. A virus-specific response was considered positive when ≥0.05% of the cells produced IFN-γ after background reduction and if the response was larger than twice the negative background signal93738.…”
Section: Methodsmentioning
confidence: 99%